2008
DOI: 10.1117/1.2841050
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of fast-moving cells in vivo using digital holographic video microscopy

Abstract: Digital in-line holography offers some significant advantages over conventional optical holography and microscopy to image biological specimens. By combining holography with digital video microscopy, an in-line holographic video microscope is developed and is capable of recording spatial 3D holographic images of biological specimens, while preserving the time dimension. The system enables high-speed video recording of fast cell movement, such as the rapid movement of blood cells in the blood stream in vivo. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Suspension cells are difficult to track using traditional microscopy as they quickly move out of focus. DHM has been used to follow a population of human endothelial cells in their 3-D trajectory through a solution (Sun et al, 2008). The cells were followed for 189 μm along the Z axis.…”
Section: Cell Migration and Motility Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspension cells are difficult to track using traditional microscopy as they quickly move out of focus. DHM has been used to follow a population of human endothelial cells in their 3-D trajectory through a solution (Sun et al, 2008). The cells were followed for 189 μm along the Z axis.…”
Section: Cell Migration and Motility Studiesmentioning
confidence: 99%
“…Sun and colleagues showed that they could follow the movement of blood cells in vivo in a tadpole blood vessel (Sun et al, 2008). This shows that DHM can be a useful tool for in vivo studies, enabling researchers to directly follow the effect of a treatment on e.g.…”
Section: Tissue Studiesmentioning
confidence: 99%
“…This unique feature has been determinant to find applications of DHM in living cell screening, [1][2][3][4] particle tracking, [5][6][7][8][9][10][11] and MEMS evaluation, [12][13][14] among many others. [15][16][17][18][19][20][21][22][23][24] The ability of performing QPI has been extended to other microscopy methods like spatial light interference microscopy or spatial light interference tomography; 25,26 hence similar applications have been reported by the use of these imaging approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Cell volume, [15][16][17] osmotic membrane water permeability coefficient, 18 and the integral intracellular refractive index 17,19 are some of the quantitative biological parameters that can be evaluated with DHM via the phase retrieving of the sample. DHM combined with digital video microscopy is also an effective tool to fully localize in three-dimensions living cells in controlled or natural environments [9][10][11] as a way to derive insight about the cell behavior. Its unique feature of label-free imaging of cells has turned DHM into a suitable tool for cell sorting and counting.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Previous 2D segmentation of digital holographic microscopy intensity reconstructions used active contours.…”
Section: Introduction Holographymentioning
confidence: 99%